Incidence and risk factors for post-stroke delirium in the elderly: A national inpatient sample (NIS) analysis - Jianrong Zhang; Mei Chen; Yaoyang Huo; Xilin Liu; Yu’e Wu; Xiaohuan Li; Jingqin Wang; Fengling Yang; Gang Liu; Hao Xie; Ying Gao (PLoS ONE, 2026)
Background Post-stroke delirium (PSD) is a critical neuropsychiatric condition affecting up to 50% of elderly patients during hospitalization, often leading to poorer outcomes. Despite its prevalence, PSD remains underrecognized in clinical practice, and national-level studies exploring its risk factors are limited. Objective To examine the incidence and risk factors associated with PSD in elderly individuals (≥65 years) using a large, nationally representative dataset. Methods Data from the Healthcare Cost and Utilization Project National Inpatient Sample (2010–2019) were analyzed. Elderly patients with a primary diagnosis of stroke were selected, and PSD was defined using the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) and ICD-10-CM codes. Multivariate logistic regression, adjusted for demographic, clinical, and hospital variables, identified independent PSD risk factors. Results Among 1,644,773 elderly stroke patients, the incidence of PSD was 19.5%. PSD occurred in 18.9% of ischemic strokes and 24.7% of hemorrhagic strokes. Patients with PSD were significantly older, with a median age of 79 years, compared to 78 years in those without PSD ( p < 0.001). They also experienced prolonged hospital stays (5 days vs. 4 days, p < 0.001), incurred greater hospitalization costs ($44,863 vs. $35,787, p < 0.001), and exhibited a higher risk of in-hospital mortality (12.6% vs. 7.0%, p < 0.001). Major risk factors for PSD include: sepsis (OR = 2.364, 95%CI = 2.329–2.400), three or more comorbidities (OR = 2.049, 95%CI = 1.984–2.116) and fluid/electrolyte disorders (OR = 1.902, 95%CI = 1.886–1.918), psychoses (OR = 1.765, 95%CI = 1.725–1.806). Conclusions PSD is frequently observed in elderly stroke patients and is associated with adverse clinical outcomes. Advanced age, comorbidities, and stroke-related complications are significant risk factors. These results underscore the importance of developing focused prevention and intervention strategies to enhance outcomes for this high-risk population.